LANGUAGE LEARNING STRATEGY ADOPTED FACULTY ECONOMICS STUDENTS LEARNING ESP MERDEKA UNIVERSITY PASURUAN - Rachmawati, Dwita Laksmita (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2017)
For the last three decades, there has been a growing interest in the learner centered approaches in the areas of second or foreign language learning. This shift was brought about by the developments taking place in other fields of education which were concerned with exploring how people think and reason. So, this study would conduct a research on the variation of language learning strategies used by first grade students at ESP (English for Specific Purposes) for Faculty of Economics, Merdeka University, Pasuruan. This study used survey study. Both quantitative and qualitative research methods are engaged in this project. The population is 140 first grade students in faculty of economics. The researcher took all of the population to be the participant of this study. Based on the findings, it can be shown that the students are the high users of overall language learning strategies. From the meanscore result, it can be shown that the students at faculty of economics employ more to the social and memory language learning strategy because the materials provided by the lecturers was related with speaking and communication skills. Keywords – Language Learning Strategy, ESP